Is 20/20 vision good enough? Visual acuity differences within the normal range predict contour element detection and integration - Keane, Brian P.; Kastner, Sabine; Paterno, Danielle; Silverstein, Steven M. (Psychonomic bulletin & review, 2015)
Contour integration (CI) combines appropriately aligned and oriented elements into continuous boundaries. Collinear facilitation (CF) occurs when a low-contrast oriented element becomes more visible when flanked by collinear high-contrast elements. Both processes rely at least partly on long-range horizontal connections in early visual cortex, and thus both have been extensively studied to understand visual cortical functioning in aging, development, and clinical disorders. Here, we ask: Can acuity differences within the normal range predict CI or CF? To consider this question, we measured binocular visual acuity and compared subjects with 20/20 vision to those with better-than-20/20 vision (SharpPerceivers) on two tasks. In the CI task, subjects located an integrated shape embedded in varying amounts of noise; in the CF task, subjects detected a low-contrast element flanked by collinear or orthogonal high-contrast elements. In each case, displays were scaled in size to modulate element visibility and spatial frequency (4–12 cycles/deg). SharpPerceivers could integrate contours under noisier conditions than the 20/20 group ( p = .0002), especially for high spatial frequency displays. Moreover, although the two groups exhibited similar collinear facilitation, SharpPerceivers could detect the central target with lower contrast at high spatial frequencies ( p <. 05). These results suggest that small acuity differences within the normal range—corresponding to about a one line difference on a vision chart—strongly predict element detection and integration. Furthermore, simply ensuring that subjects have normal or corrected-to-normal vision is not sufficient when comparing groups on contour tasks; visual acuity confounds also need to be ruled out.